Findings of the Association for Computational Linguistics: ACL-IJCNLP 2021 2021
DOI: 10.18653/v1/2021.findings-acl.4
|View full text |Cite
|
Sign up to set email alerts
|

LUX (Linguistic aspects Under eXamination): Discourse Analysis for Automatic Fake News Classification

Abstract: The democratization/decentralization of both the production and consumption of information has resulted in a subjective and often misleading depiction of facts known as Fake News -a phenomenon that is effectively shaping the perception of reality for many individuals. Manual fact-checking is time-consuming and cannot scale and although automatic factchecking, vis a vis machine learning holds promise, it is significantly hindered by a deficit of suitable training data. We present both a novel dataset, VERITAS(V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This includes using syntactic, lexical, semantic, discursive, and morphological features; but also other properties of text, such a readability, similarity, punctuation, quality, informality, subjectivity, diversity, uncertainty, complexity, specificity, sentiment, and emotions. It has been found that part-of-speech counts, lexical diversity, informality and readability are some of the most distinctive features of fake news (Azevedo, D'aquin, Davis, & Zarrouk, 2021;Castelo et al, 2019). Conversely, stylometry can be learned by disinformers in order to replicate the styles of reliable news, as shown in (Schuster, Schuster, Shah, & Barzilay, 2020), which calls for approaches that continuously update over time.…”
Section: Natural Language Processing For Stylistic Characterizationmentioning
confidence: 99%
“…This includes using syntactic, lexical, semantic, discursive, and morphological features; but also other properties of text, such a readability, similarity, punctuation, quality, informality, subjectivity, diversity, uncertainty, complexity, specificity, sentiment, and emotions. It has been found that part-of-speech counts, lexical diversity, informality and readability are some of the most distinctive features of fake news (Azevedo, D'aquin, Davis, & Zarrouk, 2021;Castelo et al, 2019). Conversely, stylometry can be learned by disinformers in order to replicate the styles of reliable news, as shown in (Schuster, Schuster, Shah, & Barzilay, 2020), which calls for approaches that continuously update over time.…”
Section: Natural Language Processing For Stylistic Characterizationmentioning
confidence: 99%
“…Early studies on fake news detection have attempted to exploit various approaches to extract features from news content and social context information, including linguistic features (Potthast et al, 2018;Azevedo et al, 2021), visual clues (Jin et al, 2016), temporal traits (Kwon et al, 2013Ma et al, 2015), user behaviors and profiles (Castillo et al, 2011;Ruchansky et al, 2017;Shu et al, 2019b). Subsequent studies have employed neural networks to automatically learn deep feature representations from similar sources of data (Ma et al, 2016;Popat et al, 2018;Nguyen et al, 2020;Kaliyar et al, 2021;Sheng et al, 2022).…”
Section: Related Workmentioning
confidence: 99%
“…Others are created from scratch with a tempting caption to enhance website traffic and visits. Recently, there have been several works girding fake news features analysis [2,3,4,5,6,7]. A veritably complex task consists to supervise and investigate the diffusion's information sources and the nature of profit users.…”
Section: Introductionmentioning
confidence: 99%